2000
DOI: 10.1037/1099-9809.6.1.42
|View full text |Cite
|
Sign up to set email alerts
|

Self-efficacy and HIV-related risk behaviors among multiethnic adolescents.

Abstract: A cross-sectional correlational design was used to investigate (a) self-efficacy and risk behaviors related to HIV; (b) the comparative predictiveness of self-efficacy and knowledge, attitudes, and beliefs regarding sexual activity and substance use; and (c) possible risk profiles for HIV among adolescents. High school students (N = 427), ranging in age from 12 to 20 years and attending Family Life Education classes in Alameda, California, volunteered to complete a self-administered questionnaire, resulting in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 35 publications
3
30
0
Order By: Relevance
“…Faryna and Morales stress that the development of theory related to adolescent sexual risk behavior requires the incorporation of culture and racial identity [16]. This and other elements of self-pride, including self-esteem and body image, are important protective factors associated with reduced sexual risk during adolescence [17].…”
Section: Youth Mediatorsmentioning
confidence: 99%
“…Faryna and Morales stress that the development of theory related to adolescent sexual risk behavior requires the incorporation of culture and racial identity [16]. This and other elements of self-pride, including self-esteem and body image, are important protective factors associated with reduced sexual risk during adolescence [17].…”
Section: Youth Mediatorsmentioning
confidence: 99%
“…First, the explanation could be due to a number of methodological factors. We included sexual abstainers in the analyses and previous reports indicate that sexually active youths score higher on measures of self-efficacy (Faryna and Morales, 2000), the same type of behavioral skills measure used in this study. Sexually abstinent teens may be less likely to report efficacy to engage in preventive behaviors, because they do not plan to have sex at all.…”
Section: Discussionmentioning
confidence: 99%
“…Eleven reports examined the empirical relationship between self-efficacy and sexual behavior. Seven studies found protective effects of self-efficacy to negotiate safer sex [38], resist peer pressure to have sex [65], delay initiation of sexual intercourse [67], avoid sexual activity or risky sexual behavior [29,69,72], and to remain abstinent [58]. However, five reports revealed no effects of selfefficacy or perceived behavioral control on various sexual behavior/intention outcomes such as sexual intercourse intention, engaging in risky sexual behavior, ever having had sex, or refusing unwanted sex [13,18,38,57,64].…”
Section: Skillsmentioning
confidence: 90%